Formulation of Analog Rice High in Fiber and Protein Based on Corn and Sorghum with the Addition of Moringa Leaves: A Review - Akbar Rifki Ferdiansyah; Heny Kusumayanti; Muhammad Amyra Faiz (Vocational College of Universitas Diponegoro, 2026)
Reliance on refined white rice as the dominant staple in many developing nations has been linked to dietary imbalances, particularly a lack of protein, fiber, and essential micronutrients. One potential alternative is analog rice, which is created from non-rice flours through extrusion or cold-molding methods and offers opportunities to diversify diets while supporting the utilization of indigenous crops. This review focuses on the development of analog rice formulated with corn (Zea mays) and sorghum (Sorghum bicolor) as primary bases, supplemented with Moringa oleifera leaf powder to enhance its nutritional value in terms of protein, fiber, and micronutrient content. Corn plays a vital role in providing starch functionality required during extrusion, sorghum contributes additional dietary fiber and phytochemicals, and Moringa leaves supply concentrated amounts of protein, minerals, and vitamins. Research indicates that incorporating Moringa at moderate levels (approximately 2–8%) enhances the nutrient profile without majorly affecting consumer perception, while higher inclusion rates often introduce bitterness and a greenish hue that lower acceptability. This article consolidates evidence on nutritional outcomes, production techniques, sensory limitations, and directions for further investigation, with particular focus on extrusion conditions, nutrient preservation, anti-nutritional factors, and consumer responses. Combining corn, sorghum, and Moringa shows considerable promise for generating functional staple foods with superior nutritional attributes, though additional studies remain necessary regarding nutrient bioavailability, clinical efficacy, storage behavior, and strategies for broader market adoption.